Peran Pemerintah Nagari dalam Pengelolaan Objek Wisata Luak Gadang di Nagari Kamang Hilia - Fauzi Fauzi; Jumiati Jumiati (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
This study aims to determine the role of the Nagari Kamang Hilia Government in managing the Luak Gadang tourist attraction. This research was conducted using a qualitative method with a qualitative descriptive type. In determining the informants by using purposive sampling methods and techniques. While the data analysis technique used by the researcher is data reduction, then data presentation and verification and drawing conclusions. The results showed that the role played by the Nagari Kamang Hilia Government in the management of the Luak Gadang tourist attraction, namely as a motivator, facilitator, and dynamist, was in accordance with the process. However, there are still obstacles faced by the Nagari Kamang Hilia Government, such as the lack of budget, supporting facilities for tourism objects, and also the lack of synergy with third parties. Therefore, the Nagari Kamang Hilia government must be more active in managing the Luak Gadang tourist attraction, so that this tour has competitiveness and is for the convenience of visiting tourists.